Estrategias metodológicas para la enseñanza de la educación física online en niños de 9 a 11 años de la Escuela de Educación Básica Roberto Rodríguez Bodero provincia del Guayas, cantón Jujan, periodo 2021-2022 - Pérez Navarro, Ángelo Omar (2022)
This research on methodological strategies for teaching physical education online in children from 9 to 11 years of age at the "Roberto Rodríguez Bodero" basic education school, Guayas province, Jujan canton, period 2021 - 2022, has the purpose of improving learning Physical Education. The study is carried out is structured by different chapters that go from the approach of the problem to the relationship that exists with the solution that arises in it. The project is based on theoretical bases that are the support on which the research is based. Consistent research methods were applied that, together with the data collection instruments, clear and precise results were obtained and which in turn served to propose as a tentative solution proposal consists of the development of an ICT Strategy Guide, which will help the teacher to teacher to improve their classroom work and thereby make school performance in the area of Education more efficient.